A Context Manager for General-Purpose Operating Systems - Olsen, Diogo; Maziero, Carlos (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Context-Aware Computing aims at making computing systems able to capture context information and to adapt to it, providing context-related services and information to users. Context is any information used to characterize in some sense a person, object, or place of interest for a given user or application. Initial definitions of context-aware computing date from twenty years ago, but until now it was not yet fully made available to end users. This paper proposes a generic model of a context manager for general-purpose operating systems, alongside with its implementation and first evaluation results. This model includes methods for building, storing, and managing contexts, and an API to make such information available to applications and users.